Performance comparison of the artificial neural network and the k-nearest neighbor classifiers in classroom speech intelligibility prediction application - M. Ridhwan, Tamjis; M. Naufal, Mansor; Pandiyan, Paulraj Murugesa, Prof. Madya Dr.; Sazali, Yaacob, Prof. Dr.; Ahmad Nazri, Abdullah, Prof. Madya Dr.; Boon, Raymond Whee Heng, Prof. Dr. (Science Academy, 2011)
Link to publisher's homepage at http://sciacademypublisher.com/